'Race’, Deprivation and the Research Agenda: Revisiting Housing, Ethnicity and Neighbourhoods - Markkanen, Sanna; Harrison, Malcolm (Routledge, 2013)
Building on a general account of recent changes and on local case study material, thispaper develops an overview of contemporary issues in the interconnected research domains of UKethnic relations, disadvantage and housing neighbourhoods. It aims to contribute to some rethinkingof ethnic disadvantage and discrimination within analytical frameworks, while looking towardsmore defensible research strategies. Matters referred to in our overview of change includeregulatory developments, diversities within and between settled minority ethnic groups, changedpatterns of in-migration, disadvantage amongst low-income white households and convergencebetween ethnic groups in internal socio-economic differentiation. A West Midlands case study usedto complement this broad coverage provides reminders of shared problems across ethnicboundaries, and of the merits of caution when hypothesising causative links between deprivation andethnicity in disadvantaged areas. The section ‘Towards Better Research Practice?’ discussesresearch approaches and priorities, suggesting that it may be useful to revisit the ‘traditionalrepertoire’ deployed in the UK ethnic relations and housing.